Evaluation of antioxidant and antimutagenic activity of herbal teas from native plants used in traditional medicine in Argentina - Carabajal, Monica Patricia Antonella (2017)
The Jarilla species are commonly used in Argentinean local communities to heal different ailments and are frequently used as infusions or decoctions. Herbal mixture infusions composed of Zuccagnia punctata Cav. (Zp), Larrea cuneifolia Cav. (Lc), Larrea divaricata Cav. (Ld), also incorporating an exotic plant species Hovenia dulcis Thunb. (H), were developed and the total phenolic and flavonoid content, antioxidant activity and mutagenic/antimutagenic capacity were analyzed and compared with the single-plant teas. The phenolic contents ranged from 29.5 mg GAE/l to 1139 mg GAE/l, and the flavonoid content was between 20.1 and 62 mg EQ/l. The mixture with higher content of H. dulcis (H mix) infusion showed the highest preference score in a sensory evaluation. Free radical scavenging capacity was determined by the ABTS assay and the most active was the mixture with equal quantities of each plant species (1/4 mix infusion). None of the plant extracts showed mutagenic effects against Salmonella typhimurium tester strains TA98 and TA100 with and without metabolic activation. The antimutagenic properties against a direct mutagen, 4-nitro-o-phenylendiamine (4-NPD), of three herbal mixtures showed about 30% of inhibition of mutagenicity. Four phenolic compounds were identified in the infusions prepared with the plant mixtures. The developed beverages in this work could be important dietary sources of antioxidant and antimutagenic compounds for prevention of chronic diseases.